SOUTH SUMATRA LRT (LIGHT RAIL TRANSIT) DEVELOPMENT PROJECT GOVERNANCE STUDY - Rumapea, Lidia Corry; Suryanto, Krishna; Jayady, Arman (Ridwan Institute, 2024)
The South Sumatra Light Rail Transit (LRT) is a short-term solution to welcome the 2018 Asian Games, but also as a long-term strategic step to overcome the transportation problem in Palembang, Indonesia. This research aims to understand the effectiveness of project governance and the obstacles faced in the implementation of the project. The data were collected through semi-structured interviews with stakeholders, direct observation at the project site, and document studies involving various official reports and regulations related to project governance. Data analysis was carried out by coding and identifying the main themes, then compared with international governance standards, namely ISO 21500:2012 and ISO 21502:2020, to assess the extent to which the project's governance was in accordance with applicable standards. The findings are expected to provide recommendations for improving project governance in infrastructure development across Indonesia, ensuring projects are completed on time, within budget, and with minimal social impact.